Evaluation of pine biomass calcination effectiveness through a boiler - Thives, Felipe César Faedo; Rohden, Abrahão Bernardo (Brazilian Journal of Production Engineering, 2025)
The search for alternatives that enable the use of renewable energy has become a major challenge regarding the effective use of all raw materials. Forest biomass has emerged as an economically viable option due to its abundance. Several companies use this material to generate thermal energy, yet there is an underuse of woody biomass. Therefore, the objective of this study was to evaluate the effectiveness of calcining pine biomass through its combustion in a boiler. The methodology consisted of a case study in a timber company that uses a boiler to generate thermal energy and this transformation generates wood ash. The ash was calcined at varying times and temperatures, investigating the homogeneity and efficiency of mass loss in each treatment. The results indicated that with longer times and temperatures better results were obtained, reaching complete homogenization of the ash sample with 5 hours and 700° C, as well as the same treatment being the most effective in mass loss with 44.34%. The conclusion showed that time was more effective than temperature, and that the ash studied was underused, having the potential to maximize thermal benefit.
Keywords: Biomass; Wood ash; Energy efficiency